Small extracellular vesicles deliver TGF‐β1 and promote adriamycin resistance in breast cancer cells - Chunli Tan; Wenbo Sun; Zhi Xu; Shuyi Zhu; Weizi Hu; Xiumei Wang; Yanyan Zhang; Guangqin Zhang; Zibin Wang; Yong Xu; Jinhai Tang (Molecular Oncology, 2021)
Chemotherapeutic resistance is a major obstacle in the control of advanced breast cancer (BCa). We have previously shown that small extracellular vesicles (sEVs) can transmit adriamycin resistance between BCa cells. Here, we describe that sEV‐mediated TGF‐β1 intercellular transfer is involved in the drug‐resistant transmission. sEVs were isolated and characterized from both sensitive and resistant cells. sEVs derived from the resistant cells were incubated with the sensitive cells and resulted in transmitting the resistant phenotype to the recipient cells. Cytokine antibody microarray revealed that most metastasis‐associated cytokines present at the high levels in sEVs from the resistant cells compared with their levels in sEVs from the sensitive cells, particularly TGF‐β1 is enriched in sEVs from the resistant cells. The sEV‐mediated TGF‐β1 intercellular transfer led to increasing Smad2 phosphorylation and improving cell survival by suppressing apoptosis and enhancing cell mobility. Furthermore, sEV‐mediated drug‐resistant transmission by delivering TGF‐β1 was validated using a zebrafish xenograft tumor model. These results elaborated that sEV‐mediated TGF‐β1 intercellular transfer contributes to adriamycin resistance in BCa.